The effect of high load training on psychomotor speed - Nederhof, E.; Lemmink, K.; Zwerver, J.; Mulder, T. (International Journal of Sports Medicine, 2007)
The purpose of the present study was to investigate whether overreached athletes show psychomotor slowness after a period of high load training. Fourteen well-trained cyclists (10 male, 4 female, mean age 25.3 [SD = 4.1] years, mean maximal oxygen consumption 65.5 [SD = 8.1] ml/kg · min) performed a maximal graded exercise test on a cycle ergometer, filled out two questionnaires and performed two tests of psychomotor speed before and after high load training and after two weeks of recovery training. A control group performed the two tests of psychomotor speed on the same occasions without changing physical activity levels. Five cyclists were classified as functional overreached, seven cyclists were classified as well-trained and two cyclists were excluded from analysis. Results showed no significant differences in psychomotor speed between the control, well-trained and functional overreached groups on the three measurements. A trend towards psychomotor slowness was found for the functional overreached compared to the control group after high load training. Additional research with more subjects and a greater degree of overload training is necessary to more conclusively determine if psychomotor speed can be used as an early marker for overtraining.